The nest that wren built - Sonenshine, Randi, 1968-; Hunter, Anne (Somerville, Massachusetts : Candlewick Press, 2020)
In the rhyming style of "The House That Jack Built," this poem about the care and specificity that Carolina wrens put into building a nest is at once tender and true to life.
Includes glossary and wren facts.
4-8 years.
Preschool-Grade 3.
Keywords: Wrens -- Juvenile fiction; Animals -- Juvenile fiction; Stories in rhyme